2013
DOI: 10.1073/pnas.1217727110
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Bin, Amphiphysin, and RSV161/167 (BAR) domain of ACAP4 regulates membrane tubulation

Abstract: ArfGAP With Coiled-Coil, Ankyrin Repeat And PH Domains 4 (ACAP4) is an ADP-ribosylation factor 6 (ARF6) GTPase-activating protein essential for EGF-elicited cell migration. However, how ACAP4 regulates membrane dynamics and curvature in response to EGF stimulation is unknown. Here, we show that phosphorylation of the N-terminal region of ACAP4, named the Bin, Amphiphysin, and RSV161/167 (BAR) domain, at Tyr34 is necessary for EGF-elicited membrane remodeling. Domain structure analysis demonstrates that the BAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…S3A; lanes 2-3 vs. 1). It has been reported that stimulation with epidermal growth factor (EGF) promotes membrane association of the BAR domain (35). We confirmed EGFR expression in our HEK293T cells, and EGFR level is down-regulated upon EGF stimulation as previously reported by Hong et al (36) (Supplemental Fig.…”
Section: Ptena Interacts With Endocytic Proteins and Regulates Endocysupporting
confidence: 91%
“…S3A; lanes 2-3 vs. 1). It has been reported that stimulation with epidermal growth factor (EGF) promotes membrane association of the BAR domain (35). We confirmed EGFR expression in our HEK293T cells, and EGFR level is down-regulated upon EGF stimulation as previously reported by Hong et al (36) (Supplemental Fig.…”
Section: Ptena Interacts With Endocytic Proteins and Regulates Endocysupporting
confidence: 91%
“…A large number of cytosolic proteins are known to be activated and transduce signals upon phosphorylation or the addition of a charge to the protein. Recently, the BAR domains of ACAP4 have been reported to be activated by phosphorylation during membrane association in a manner dependent on epidermal growth factor (EGF) stimulation (333). However, when we consider the increase of negative charge brought by phosphorylation, the consequence might be the opposite, because an addition of negative charge may enhance repulsion from anionic lipids of the membrane.…”
Section: F How Is the Bar Domain Superfamily Regulated?mentioning
confidence: 99%
“…Dry glue was prepared through Coomassie blue staining, and the phosphor screen was pressed. A typhoon scanner was used for data analysis (Ren and Dai , Zhang et al , Zhao et al )…”
Section: Methodsmentioning
confidence: 99%